2014
DOI: 10.1016/j.biomaterials.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Micropattern width dependent sarcomere development in human ESC-derived cardiomyocytes

Abstract: In this study, human embryonic stem cell-derived cardiomyocytes were seeded onto controlled two-dimensional micropatterned features, and an improvement in sarcomere formation and cell alignment was observed in specific feature geometries. High-resolution photolithography techniques and microcontact printing were utilized to produce features of various rectangular geometries, with areas ranging from 2,500μm2 to 160,000μm2. The microcontact printing method was used to pattern non-adherent poly(ethylene glycol) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
121
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(123 citation statements)
references
References 58 publications
(43 reference statements)
2
121
0
Order By: Relevance
“…We anticipate that the simplicity of our approach using modular peptide-presenting surfaces will facilitate multifactorial screens to determine the combinatorial effects of insoluble and soluble signaling on stem cell fate. Defined surfaces that support cardiomyocyte differentiation (i.e., GBP-presenting surfaces), and the selectable H9 cTnT-GFP cell line we derived, will be useful tools study cardiogenesis (47). Many differentiation protocols rely on different stages in which the soluble factors are changed over time.…”
Section: Discussionmentioning
confidence: 99%
“…We anticipate that the simplicity of our approach using modular peptide-presenting surfaces will facilitate multifactorial screens to determine the combinatorial effects of insoluble and soluble signaling on stem cell fate. Defined surfaces that support cardiomyocyte differentiation (i.e., GBP-presenting surfaces), and the selectable H9 cTnT-GFP cell line we derived, will be useful tools study cardiogenesis (47). Many differentiation protocols rely on different stages in which the soluble factors are changed over time.…”
Section: Discussionmentioning
confidence: 99%
“…Human-induced pluripotent stem cell-derived CMs were obtained as follows. Gibco Episomal hiPSC Line was induced to differentiate by biphasic modulation of Wnt signalling33. Briefly, cells were routinely grown on Matrigel coated plates in Essential 8 medium.…”
Section: Methodsmentioning
confidence: 99%
“…Although PSC-CMs can be efficiently induced from PSCs (Kattman et al, 2011; Uosaki et al, 2011), proper maturation of PSC-CMs remains a critical hurdle for recapitulating the adult phenotype. Recent studies have suggested long-term culture, extrinsic stimuli, or culturing on micropatterned substrates may improve cell morphology and enhance CM maturation (Lundy et al, 2013; Salick et al, 2014; Yanagi et al, 2007; Yang et al, 2014). However, whether these cells truly mature for meaningful use as a model for adult-heart diseases has not been established.…”
Section: Introductionmentioning
confidence: 99%